1998
DOI: 10.1136/gut.43.5.669
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor assessment of endoscopically removed malignant colorectal polyps

Abstract: Background-Malignant colorectal polyps are defined as endoscopically removed polyps with cancerous tissue which has invaded the submucosa. Various histological criteria exist for managing these patients. Aims-To determine the significance of histological findings of patients with malignant polyps. Methods-Five pathologists reviewed the specimens of 85 patients initially diagnosed with malignant polyps. High risk malignant polyps were defined as having one of the following: incomplete polypectomy, a margin not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
4
25

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 29 publications
1
122
4
25
Order By: Relevance
“…In 23 series, [14][15][16][17][18][19][20][21][22][24][25][26][27]29,[31][32][33][34][35]38,[40][41][42] clinical or endoscopic follow-up data were available, ranging from 12 to 90 (median, 60) months, and accounting for 1,535 (80.1 percent) of the included polyps. Regarding endoscopic data, polyp site was clearly specified in 17 series, accounting for 1,461 polyps.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In 23 series, [14][15][16][17][18][19][20][21][22][24][25][26][27]29,[31][32][33][34][35]38,[40][41][42] clinical or endoscopic follow-up data were available, ranging from 12 to 90 (median, 60) months, and accounting for 1,535 (80.1 percent) of the included polyps. Regarding endoscopic data, polyp site was clearly specified in 17 series, accounting for 1,461 polyps.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Polyp morphology was available in 19 series, enrolling 1,145 polyps. 1 [39][40][41][42] Finally, cancerrelated death was reported in 56 (3.6 percent) of those 1,535 patients for whom follow-up data were available, with an interval from the diagnosis ranging from 5 to 101 (median, 32) months. Death because of surgical complications, inferred from 28 studies, was reported in 8 (0.8 percent) of 951 operated patients.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 3 more Smart Citations